1992
DOI: 10.1007/bf02066985
|View full text |Cite
|
Sign up to set email alerts
|

Results of pouch surgery after ileo‐anal anastomosis: The implications of pouchitis

Abstract: The ileal pouch-anal operation is the procedure of choice for those suitable patients requiring surgery for chronic ulcerative colitis or familial adenomatous polyposis. The functional results are generally good but pouchitis remains a significant and poorly understood complication. This review encompasses factors relating to pouchitis, e.g., bacteriological, functional and histological changes, with emphasis on its biology and treatment, and the long-term implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…"Pouch ileitis" was first described by Kock The frequency of occurrence of pouchitis is estimated to be as high as 50%2,3 in ileoanal continent reservoirs and 43% in Kock pouches. "4 However, there is wide variability of reporting in the literature, which may be due to a lack of [5][6][7][8] accepted diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…"Pouch ileitis" was first described by Kock The frequency of occurrence of pouchitis is estimated to be as high as 50%2,3 in ileoanal continent reservoirs and 43% in Kock pouches. "4 However, there is wide variability of reporting in the literature, which may be due to a lack of [5][6][7][8] accepted diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pouchitis is the result of bacterial overgrowth, particu larly of anaerobic bacteria, secondary to stasis in the ileal pouch (53)(54)(55)(56). The generally satisfactory response to treatment with metronidazole supports this hypothesis.…”
Section: Pouchitismentioning
confidence: 94%
“…According to Fozard and Pemberton the majority of patients respond rapidly to a short course of treatment. 28 In their series only 3% of the patients were refractory to this therapy or had severe side effects. O'Connell reported that all his patients with pouchitis obtained prompt relief of symptoms.…”
Section: Treatmentmentioning
confidence: 97%
“…Although pouchitis has been reported to occur before ileostomy closure, this complication is seen predominantly after ileostomy closure . 28 Another intriguing observation is that pouchitis appears confined to patients operate d on for ulce rative colitis, whether the pouch is placed in the pelvis or constructe d as a continent ileostomy. 34 However, in 1990 Kmiot et al 35 reported a fully documented case of pouchitis in a patient following ileal reservoir construction for familial adenomatous polyposis.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation